RELATIONSHIP BETWEEN UNITS AND FORMING PECTINS ALGINATES, BIOADSORBENTES MATERIALS AND BOSORPTION OF CU (II) - Tapia H., Nelson (2008)
The adsorbent capacity of biomasses pre-treated has been evaluated, containing pectin and alginate. The orange shells and lemon and the nopal palmets were dried and crushed, before being treated with NaOH to produce the demetoxilation of the pectin. For the reticulation of the polysaccharides they become agitated the biopolymers with a solution 0,2 M of CaCl2, improving their mechanical stability. The good pH in the process of biosorption of the Cu (II) it was in the range from 4 to 4.5. The capacity of biosorption of these biomasses was evaluated in assays type batch. The biosorption isotherms are described by the models of Langmuir, being obtained a maximum capacity of adsorption of 68,97 mg/g and equilibrium constant of 0,093.